Diaspora Indonesia-Filipina sebagai Aktor Multi-Track Diplomacy dalam Diplomasi Ekonomi dan Perdagangan - Rara Gusnita Putri (Lampung Center for Global Studies (LCGS), 2025)
Abstract In July 2012, the first Indonesian Diaspora congress was held in Los Angeles, United States. The congress, which was attended by various Diasporas from all over the world, produced the Indonesian Diaspora Declaration which raised enthusiasm to become a developed and prosperous country. Apart from that, from this congress, the Indonesian Diaspora Network Global (IDN Global) was formed. IDN Global was formed at the second congress in Jakarta, August 2013. IDN Global is spread across more than 50 countries, including one of them, the Philippine Chapter of IDN Global or better known as the Indonesia-Filipina Diaspora. By using a descriptive qualitative approach, it is explained that the Indonesia-Filipina Diaspora supports Indonesian and Philippine diplomacy in the fields of economics and trade. Economic diplomacy and trade are important aspects in bilateral relations between Indonesia and the Philippines, where one element that is increasingly being taken into account in strengthening relations between the two countries is the role of the Indonesian diaspora in the Philippines. Currently, the Indonesia-Filipina Diaspora as part of a broader diplomatic strategy is considered to be able to play a role as an actor in multi-track diplomacy. Apart from that, the presence of the Indonesian diaspora in the Philippines can also increase Indonesia's economic growth and contribute to the nation's progress. Keywords: Indonesian Diaspora Network Global (IDN Global), Indonesia-Filipina Diaspora, Multi-track Diplomacy, Economic and Trade Diplomacy